Implementation of Stunting Prevention Policy in Tanjung Village, Nguter District, Sukoharjo Regency - Sri Riris Sugiyarti (Indonesian Journal Publisher, 2025)
Stunting is a chronic nutritional problem that affects children's growth and development, particularly in physical and cognitive aspects. This condition remains a challenge in various regions, including Tanjung Village, Nguter District, Sukoharjo Regency. This research aims to describe and analyze the implementation of stunting prevention policies in Tanjung Village based on George C. Edwards III's implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The research uses a descriptive qualitative approach with data collection methods through observation, in-depth interviews, and documentation. Informants were purposively selected, consisting of village midwives, health cadres, village officials, and Puskesmas Nguter staff. The research results show that the policy implementation has been progressing quite well. Cross-sector communication is actively carried out through socialization and counseling. Human resources and supporting facilities are available, although limited by the budget. The disposition of the implementers shows a positive attitude and high commitment in executing the program. The bureaucratic structure has been equipped with Standard Operating Procedures (SOP), but there are still obstacles in the compliance of the implementers with work standards. Overall, the implementation of stunting prevention policies in Tanjung Village shows a positive direction, but still requires strengthening, especially in terms of resources and consistency of execution